2023
DOI: 10.1536/ihj.23-116
|View full text |Cite
|
Sign up to set email alerts
|

The First Case in Japan of Fulminant Myocarditis Due to Multisystem Inflammatory Syndrome in Children (MIS-C) That Required Mechanical Circulatory Support

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a novel hyperinflammatory syndrome that is associated with severe acute respiratory syndrome coronavirus 2 infections. Reports describing the mechanical circulatory support (MCS) and myocardial biopsy for fulminant myocarditis due to MIS-C are limited.A 13-year-old male patient with MIS-C underwent treatment, including immunosuppressive therapy and MCS devices, and managed to recover from pulseless electrical activity cardiac arrest. This is the first pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The prevalence of MIS-C is lower in Asian countries including Japan compared with that in the United States and Europe, although the prevalence of KD is much higher in Japan. 10 These findings indicate that this discrepancy might be caused by the racial differences in immune responses for SARS-CoV2 infection. Furthermore, the small sample size in this study might be a cause of this discrepancy.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of MIS-C is lower in Asian countries including Japan compared with that in the United States and Europe, although the prevalence of KD is much higher in Japan. 10 These findings indicate that this discrepancy might be caused by the racial differences in immune responses for SARS-CoV2 infection. Furthermore, the small sample size in this study might be a cause of this discrepancy.…”
Section: Discussionmentioning
confidence: 97%
“…Surprisingly, large MIS‐C cohort studies from China, Japan, the Philippines, Thailand, Malaysia, and others were not identified. Extreme cases reported from Japan have shown the need for extracorporeal membrane oxygenation and continuous hemodiafiltration for MIS‐C‐related acute myocardial and renal injury and the potential benefit of infliximab in a patient with refractory MIS‐C 47–50 …”
Section: Discussionmentioning
confidence: 99%